MENINGKATNYA PERMOHONAN DISPENSASI KAWIN DI PENGADILAN AGAMA PANYABUNGAN MASA PANDEMI COVID 19 (TINJAUAN YURIDIS) - Darania Anisa (IAIN Padangsidimpuan, 2022)
Marriage data in Indonesia during the Covid-19 pandemic shows an increase in both the marriages of couples who are old enough and those who are still underage. Especially for underage couples who are Muslim and want to get married, they must apply for a marriage dispensation to the Religious Court. Data on applications for marriage dispensation from the Superme Court in 2019 were 23,126 applications, increasing to 64,211 applications in 2020. The increase in applications for marriage dispensation during the COVID-19 pnademic was motivated by the change in the marriage age limit for prospective brides to 19 (Nineteen) years, and the existence of PERMA Number 5 of 2019 which specifically regulates related to adjudicating applications for marriage dispensation. Several other factors, the impact of the COVID-19 pandemic, were seen from the reasons the applicants applied for a marriage dispensatoin due to local cultural customs (marlojong) and because they had had sex and even got pregnant out of wedlock. The granting of a marriage dispensation at the Panyabungan Religiuos Court prioritizes the readiness and benefit of the applicant.